2022
DOI: 10.3389/fimmu.2022.902017
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Immune-Mediated Mechanisms of Gastric Carcinogenesis Through Single-Cell RNA Sequencing

Abstract: Single-cell RNA sequencing (scRNAseq) technology is still relatively new in the field of gastric cancer immunology but gaining significant traction. This technology now provides unprecedented insights into the intratumoral and intertumoral heterogeneities at the immunological, cellular, and molecular levels. Within the last few years, a volume of publications reported the usefulness of scRNAseq technology in identifying thus far elusive immunological mechanisms that may promote and impede gastric cancer develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…A low sequencing depth in scRNA‐seq presents challenges in detecting lowly expressed genes and alternative splicing events 31 . Furthermore, certain cell types, such as granulocytes, prove challenging to target due to their low RNA content and high levels of ribonuclease (RNase) 41 . Collectively, these challenges contribute to the complexities and limitations associated with scRNA‐seq analysis in gastric tumours.…”
Section: Resultsmentioning
confidence: 99%
“…A low sequencing depth in scRNA‐seq presents challenges in detecting lowly expressed genes and alternative splicing events 31 . Furthermore, certain cell types, such as granulocytes, prove challenging to target due to their low RNA content and high levels of ribonuclease (RNase) 41 . Collectively, these challenges contribute to the complexities and limitations associated with scRNA‐seq analysis in gastric tumours.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging technologies such as single-cell RNA-sequencing (scRNA-seq) are delivering unprecedent insights of elusive immune-mediated mechanisms of gastric carcinogenesis by providing a comprehensive view of the cellular landscape and interactions within a tissue at a single-cell resolution, with the potential to contribute towards the development of more effective diagnostics and therapeutic targets (102)(103)(104).…”
Section: Microbiota Interplay In Gastric Carcinogenesismentioning
confidence: 99%
“…Subsequent studies also showed that TEC participated in the formation of tumor immune tolerance under hypoxia ( 66 ). TEC can interact with CAF through VEGFA in GC ( 67 ).In other tumors, TEC can up regulate the immune checkpoint molecules of T cells and inhibit the activation of T cells ( 68 ). TEC expressing FasL can reduce the number of CD8 + T cells and increase the number of Treg ( 69 ).…”
Section: The Constitution Of Gc Tmementioning
confidence: 99%